Research on the Settlement Regulation and Stability of Large Building Foundation over Gobs: A Case Study in the Xiangcheng Coal Mine, China - Wenyan Guo; Bingnan Hu; Junying Zhang; Qingtong Chen; Xinguo Jia; Jianghua Li (Shock and Vibration)
Due to the acceleration of urbanization in China, the land use and new building construction in mining subsidence areas are increasing. However, a large high-rise building (100 m × 80 m × 100 m) was planned to be built above gob areas in the Xiangcheng Mine subsidence area. According to the analysis of the borehole exploration data, borehole TV observations, and theoretical calculations, there were broken bedrock and developmental fractures in the fracture and caved zones above the gob areas. In addition, the depth affected by the building load is less than 9 m from the top of the fracture zone; thus, the stabilities of the gobs are low. Then, through the theoretical analysis of the space stress, compression settlement of foundation soil, and residual settlement of the gob and coal pillar under loads, combining the similar simulation study on settlement characteristics of foundation soil and gobs, the total settlement of the foundation can be regarded as the vector superposition of the compression settlement and residual settlement; then, the maximum settlement is calculated as 555 mm and the maximum tilt is 14.9 mm/m under the building load, which are greater than the permissible values of 200 mm and 2 mm/m, indicating that the foundation’s stability is inadequate. Therefore, the treatment measures of the deep pile group foundations in the soil layer and grouting reinforcement in the gobs were simultaneously put forward to effectively improve the stability of the building foundations.